Association of ABO blood groups and vitiligo. - Kareemullah, L (1977)
ABO blood group frequencies of 1000 vitiligo patients were studied and compared with those of blood donors and local population. The relative risk of O was significantly reduced in patients in comparison with blood donors but not with local population. This can possibly be explained by the well-known preference of O group donors in the blood bank. On a review of other studies it was felt that there may not be any real association of ABO blood groups with vitiligo.